Institutional constraints to small farmer development in Southern Africa - Obi, Ajuruchukwu; SpringerLink (Online Service). (Wageningen Wageningen Academic Publishers, 2011)
Smallholder farming in Southern Africa has been on the decline in recent years as a result of a combination of institutional, climatic and macro-economic constraints. This has led to some of the worst food and humanitarian crisis in recent years, culminating in drastic food shortages and famines and deepening poverty. Governments and the development community are therefore concerned about the current and potential consequences of this state-of-affairs and are exploring ways and means to reverse the situation. There is increasing awareness about the role of institutions in smallholder development in the region and elsewhere on the continent. But consensus as to what specific institutions are crucial or even how they exert their influence has not yet been achieved despite a considerable amount of theoretical information now available on the subject. This chapter begins the task of defining the broad outlines of a more focused study on the role of institutions in small farmer situations in Southern Africa and proposes an analytical framework consolidated from a wide range of expert views and opinions. Brief descriptions of the diverse studies that fit that framework are provided to attempt to contribute to a debate on the feasible procedures for undertaking a comprehensive analysis of the institutional constraints faced by the small farmer in relation to market access and exploring the competitiveness of the small-scale agriculture in the region.
Preface. Abbreviations and acronyms. Exchange rates for programme countries. Part II, Background and issues on the role of institutions in smallholder development in Southern Africa -- Part II, Rural livelihood strategies and current circumstances of the small farmer in South Africa -- Part III, Socio-economic and commodity marketing factors among small farmers in South Africa -- Part IV, Marketing constraints and opportunities in specific commodity lines -- Part V, Institutional issues in natural resource management and implications for smallholder development in Southern Africa -- Part VI, Alternative trade and support arrangements to enhance livelihoods and welfare of small farmers. Appendix The methodologies of the studies. References. About the contributors. Keyword index.
Keywords: Farms, Small -- Africa, Southern; Farms, Small -- Government policy -- Africa, Southern; Rural development -- Africa, Southern; Agriculture and state -- Africa, Southern; Farm produce -- Africa, Southern -- Marketing; Natural resources -- Africa, Southern -- Management